2022
DOI: 10.1080/13880209.2022.2089694
|View full text |Cite
|
Sign up to set email alerts
|

Repair mechanism of Wuwei Fuzheng Yijing formula in di-2-ethylhexyl phthalate-induced sperm DNA fragmentation in mice

Abstract: Context Di-2-ethylhexyl phthalate (DEHP), a known persistent organic pollutant, can increase the sperm DNA fragmentation index (DFI). Objective To investigate the mechanism underlying the repair of DEHP-induced sperm DNA damage in mice by Wuwei Fuzheng Yijing (WFY) formula. Materials and methods The potential targets of WFY and sperm DNA fragment (SDF) were obtained from the TCMSP, BATMAN-TCM, OMIM and GeneCards. The protein–protein interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Existing toxicological studies on phthalates have primarily focused on their impact on the male reproductive system (Sedha et al, 2021). Phthalates have been shown to cause sperm DNA damage, leading to adverse effects on male fertility, embryo development, and pregnancy rates (Zhang et al, 2022). Considering that phthalates are commonly used in biomedical and industrial applications, it is crucial to thoroughly investigate their safety profiles prior to their use.…”
Section: Introductionmentioning
confidence: 99%
“…Existing toxicological studies on phthalates have primarily focused on their impact on the male reproductive system (Sedha et al, 2021). Phthalates have been shown to cause sperm DNA damage, leading to adverse effects on male fertility, embryo development, and pregnancy rates (Zhang et al, 2022). Considering that phthalates are commonly used in biomedical and industrial applications, it is crucial to thoroughly investigate their safety profiles prior to their use.…”
Section: Introductionmentioning
confidence: 99%
“…[ 19 ] The previous animal experiments of the research group showed that Wuwei Fuzheng Yijing Decoction can effectively reduce the DFI of mouse sperm and improve the reproductive capacity of mice. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%
“…[19] The previous animal experiments of the research group showed that Wuwei Fuzheng Yijing Decoction can effectively reduce the DFI of mouse sperm and improve the reproductive capacity of mice. [20] However, the current clinical studies have limitations in methods and sample size, and lack sufficient evidence for WFY as a supplementary treatment for sperm DNA damage in male infertility. Therefore, we aim to design a randomized controlled trial to evaluate the efficacy and safety of WFY in the treatment of sperm DNA damage in male infertility.…”
Section: Introductionmentioning
confidence: 99%